The milk of dreams = Il latte dei sogni: Biennale arte 2022 - Biennale di Venezia (59e : 2022 : Venise, Italie); Alemani, Cecilia (La Biennale di Venezia, 2022)
The colossal two-part catalog accompanying the 2022 biennial’s ambitious exploration of metamorphosis, as imagined by 213 artists from across the world Named after a children’s book by Surrealist artist Leonora Carrington, the 59th Venice Biennale takes Carrington’s fey creatures, along with other figures of transformation, as companions on an imaginary journey through the metamorphoses of bodies and slippery definitions of humanity. Volume I of this two-part publication addresses the conceptual basis of The Milk of Dreams, as developed by curator Cecilia Alemani, and further elaborates upon its thematic threads. Each artist from the 2022 Biennale is introduced by way of a critical text and an iconographic apparatus. The volume includes Alemani’s original exhibition texts and a plethora of original essays by some of today’s most cutting-edge thinkers and writers, with conversations and reprinted texts concerning the exhibition: the representation of bodies and their metamorphoses, the relationship between individuals and technologies, and the connection between bodies and the earth. Volume II of the catalog presents the participating countries and the collateral events of the biennale; its lavishly illustrated texts explore the various projects on display in Venice. Artists include: Sophia Al-Maria, Josephine Baker, Djuna Barnes, Jadé Fadojutimi, Nan Goldin, Robert Grosvenor, Tishan Hsu, Jacqueline Humphries, Allison Katz, Kapwani Kiwanga, Barbara Kruger, Hannah Levy, Liliane Lijn, Candice Lin, Precious Okoyomon, Akosua Adoma Owusu, Elle Pérez, Aki Sasamoto, Sable Elyse Smith, Kaari Upson, Andra Ursuta, Cecilia Vicuña, Marianne Vitale, Meta Vaux Warrick Fuller and Laura Wheeler Waring.
Keywords: art contemporain; arts; arts visuels et médiatiques; corps; cours; discipline; har4600; histoire de l'art; premier cycle; thématiques

Corps vivante - Delporte, Julie (Éditions Pow Pow, 2022)
"En 1990, Julie Delporte n'a encore jamais vu de butch, mais sa tante préférée chasse et fume le cigare. Presque vingt ans plus tard, elle publie un livre sur Tove Jansson dans lequel elle raconte avec joie que cette artiste finlandaise est la première femme à qui elle s'identifie, seulement elle était lesbienne et pas Julie. À 35 ans, après avoir surligné de toutes les couleurs son exemplaire de La pensée straight de Monique Wittig, Julie Delporte arrête de porter des robes et prend son avenir en main. Dans ce roman graphique qui fait suite à Moi aussi je voulais l'emporter, l'autrice retrace l'histoire de sa sexualité. Une histoire marquée par la violence malheureusement trop banale des agressions, comme par celle des clichés et des injonctions liés à une culture de la performance et de l'hétéronormativité."–
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; 2020-2029; LGBTQIA2+; amériques; approches et analyses; arts; arts visuels et médiatiques; autofiction; bande-dessinée; canada; corps; cours; discipline; europe; france; har4600; identités LGBTQIA2+; point de vue situé; premier cycle; périodes historiques; queer; québec; roman graphique; régions géographiques; sexualité; thématiques; violences; études littéraires

Elles font l'abstraction - Macel, Christine; Ziębińska-Lewandowska, Karolina; Centre Georges Pompidou; Museo Guggenheim Bilbao (Éditions du Centre Pompidou, 2021)
Mise en lumière du rôle joué par les femmes artistes dans l'essor du courant de l'abstraction au XXe siècle à travers le monde. Les recherches personnelles ou en groupe de ces femmes sont présentées. Les spécialistes élargissent leurs propos à la danse, aux arts appliqués, à la photographie, au cinéma et aux arts performatifs. Avec les notices biographiques de 115 artistes.
Keywords: 1900-1999; arts; arts visuels et médiatiques; cinéma; communication; cours; danse; discipline; femmes* artistes; har4600; histoire de l'art; histoire et politique; performance; photographie; premier cycle; périodes historiques; thématiques

Guerrilla Girls: the art of behaving badly - Guerrilla Girls (Group of artists) (Chronicle Books, 2020)
Guerrilla Girls: The Art of Behaving Badly is the first book to catalog the entire career of the Guerrilla Girls from 1985 to present. The Guerrilla girls are a collective of political feminist artists who expose discrimination and corruption in art, film, politics, and pop culture all around the world. This book explores all their provocative street campaigns, unforgettable media appearances, and large-scale exhibitions. Captions by the Guerrilla Girls themselves contextualize the visuals. Explores their well-researched, intersectional takedown of the patriarchy In 1985, a group of masked feminist avengers'known as the Guerrilla Girls'papered downtown Manhattan with posters calling out the Museum of Modern Art for its lack of representation of female artists. They quickly became a global phenomenon, and the fearless activists have produced hundreds of posters, stickers, and billboards ever since. More than a monograph, this book is a call to arms. This career-spanning volume is published to coincide with their 35th anniversary. Perfect for artists, art lovers, feminists, fans of the Guerrilla Girls, students, and activists You'll love this book if you love books like Wall and Piece by Banksy, Why We March: Signs of Protest and Hope by Artisan, and Graffiti Women: Street Art from Five Continents by Nicholas Ganz.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; artivisme; arts; arts visuels et médiatiques; com5170; corps; cours; discipline; histoire de l'art; justice sociale; militance; patriarcat; premier cycle; périodes historiques; rapports sociaux de sexe; représentation des femme*; régions géographiques; sexisme; sofia; systèmes d'oppressions; thématiques; travail; états-unis